Penanganan Covid-19 Dalam Pendekatan Kaidah Fikih dan Ushul Fikih (Analisis Kebijakan Pembatasan Sosial Berskala Besar Dibidang Keagamaan) - Shubhan Shodiq (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2020)
The corona virus are sweeping the world. Transmission that is so fast from human to human causes heavy casualties. Based on research, this virus commonly spread through droplets and direct contact with sufferers. Nowadays, vaccines and drugs are still being developed by experts. Therefore, almost all country take on policies to prevent the spread of the virus. As an affected country, Indonesia also issued a policy of Pembatasan Sosial Sekala Besar (PSBB) (Large-Scale Social Restrictions). This rule regulate various aspects such as restrictions on educational, employment and worship activities. In the rules of worship, this regulation requires temporary abolition of worship in worship place. This instruction raises the pros and cons in society. Some people consider the omission of observance in the worship place is inappropriate due to the fact that other public places such as markets are still open. Using kaidah fikih and ushul fikih approach, this paper analyzes the policy. The results of this study indicate that the policy of eliminating the worship in the worship places during a pandemic is not inapposite with Islamic law. Moreover, to issue other policies in dealing with this pandemic, based on Islamic law, safeguarding lives (hifzh al-nafs) is prioritized more than protecting assets (hifzh al-mâl).